PENGARUH PENGGUNAAN ALAT PERAGA TERHADAP MINAT BELAJAR SISWA-SISWI PAUD KRISTEN SE-KABUPATEN BANYUMAS - Dwiyono; Agus Kristiono (STTII PURWOKERTO, 2021)
In the learning process, students are guided to a specific and focused educational goal, in order to develop various potentials so that students have competencies according to the level of learning at school. For this reason, teachers as educators are expected to be able to provide maximum teaching. One of the efforts to maximize the learning process is to use teaching aids. However, there were still some teachers / school institutions who had not prepared the teaching aids optimally. This research aims to find out whether there is an effect of the use of teaching aids on the learning interest of Christian PAUD students in Banyumas Regency. The results of this research indicate that there is a significant effect of the use of teaching aids on interest in learning, the magnitude of the influence is 28.6%, the remaining 71.4% is influenced by other factors outside the author's research.